Child labour: an analysis - Gikunda, Nancy Karimi (Centre for Law and Society, 2026)
The exploitation of minors is on the rise and in recent years, there has been an awakening in the world attention to the problem of child labour. International bodies have adopted conventions and declarations on the issue while almost all states have laws, services and other activities intended to restrnin the economic exploitation of children and alleviate its effects. Despite these efforts, there exists a wide gap between laws and practice. This paper focuses on an analytical review of child labour and it exammes the underlying causes of child labour and its consequences for children and the society at large. In developing countries, the vast majority of children continue to contribute to • family economy making child laboul' economically important. Steps must however be taken to alleviate it. Not all work is bad for children.